(untitled) (Stavební obzor - Civil Engineering Journal, 2020)
Constructing over expansive soils often severely damage the structure due to high swell-shrinkage behaviour and loss of strength owing to fluctuating water content. Due to the above reasons construction on or using expansive soils is considered to be unsafe. The technique of such soil, improvement by installation of granular piles (also known as stone columns) is popular to marshy lands, marine clays, loose sand, silty or clayey sand, and compressible soils. Granular piles improve swelling properties of expansive soil. In the present study six expansive soils were used. The one of them was the naturally available black cotton soil and others were derived from it by mixing bentonite in different proportions. Test beds of these soils were prepared at different initial moisture contents and the granular pile of sand was installed in these beds by the method of removal. Besides initial moisture content, properties of expansive soils, the spacing between the piles (expressed by s/d ratio; s = spacing between the piles and d = diameter of a pile) and the relative density of granular pile forming material were the variables of the study. Multiple linear regression analysis on the test data has been performed and equations for predicting swelling pressure of soil bed without pile and inclusion with granular pile have been developed.